Effects of plyometric training on skill and physical performance in healthy tennis players: A systematic review and meta-analysis - Deng, N.; Soh, K. G.; Huang, D.; Abdullah, B.; Lou, S.; Rattanakoses, W. (Frontiers in Physiology, 2022)
Background: Plyometric training (PT) has been researched extensively in athletic populations. However, the effects of PT on tennis players are less clear.